Motivický vývoj obrazu minulosti Šumavy - Michal Hořejší (Góry, Literatura, Kultura)
The article seeks to answer the question of the historical development of the depiction of Bohemian Forestʼs past, and what motives may therefore interfere with the nature of the current discourse on the management of the Bohemian Forest National Park. To this end I analysed a corpus of nearly fifty prefaces and afterwords to mostly tourist guides to the Bohemian Forest from 1883–2013. The research itself consists of a qualitative part, based on simple reading, and a quantitative part, based on collocation and concordance corpus analysis. The result indicate that the image of the Bohemian Forestʼs past has a long-standing motif of enduring continuity ending with a break, which is often portrayed in various ways—e.g. as the accession of the Habsburgs to the Czech throne, the expulsion of the German-speaking population after 1945, the storm of 1870, or even the establishment of a national park in 1991. I find it remarkable that the competing image based on the motif of permanent continuity appears mainly in texts from the period 1945–1990.